2014
DOI: 10.1063/1.4895703
|View full text |Cite
|
Sign up to set email alerts
|

Generation of uniform large-area very high frequency plasmas by launching two specific standing waves simultaneously

Abstract: With the characteristics of higher electron density and lower ion bombardment energy, large-area VHF (very high frequency) plasma enhanced chemical vapor deposition has become an essential manufacturing equipment to improve the production throughput and efficiency of thin film silicon solar cell. However, the combination of high frequency and large electrodes leads to the so-called standing wave effect causing a serious problem for the deposition uniformity of silicon thin film. In order to address this issue,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Thus, the higher growth rate with dense film were produced. In addition, most researcher got that the higher frequency would also result in a reduced sheath thickness and a lower voltage potential across the electrodes that makes the deposition growth of films greater and provide better uniformity of films thickness [8]. Thus, the roughness of the SiC thin films is 5.43nm, 11.94nm and 13.91nm obtained at 100MHz, 160MHz and 200MHz respectively which is greatly become more compact as the frequency increased.…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…Thus, the higher growth rate with dense film were produced. In addition, most researcher got that the higher frequency would also result in a reduced sheath thickness and a lower voltage potential across the electrodes that makes the deposition growth of films greater and provide better uniformity of films thickness [8]. Thus, the roughness of the SiC thin films is 5.43nm, 11.94nm and 13.91nm obtained at 100MHz, 160MHz and 200MHz respectively which is greatly become more compact as the frequency increased.…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…In solar and display applications, large area PECVD chambers are often rectangular to accommodate rectangular substrates. These PECVD and PEALD plasmas sources have been extended to the VHF range in recent years [25].…”
Section: Rectangular Capacitively Coupled Plasma Reactormentioning
confidence: 99%
“…Both experimental [19][20][21] and numerical [22][23][24] research indicated that by varying the phase difference between the two sources applied to the top and bottom electrodes, i.e., the so-called phase-shift control, the plasma currents redistributed and therefore the plasma uniformity could be optimized. Moreover, Chen et al pointed out that the plasma nonuniformity decreased significantly by launching a traveling wave, which was generated by the superposition of two standing waves with the same amplitude and out of phase by 90 • in space and time [25][26][27]. Bera et al introduced the electric potential and the magnetic vector potential to calculate the ES field and the EM field, respectively, and they presented different electron density distributions with various combinations of powers at 60 MHz and 180 MHz [28].…”
Section: Introductionmentioning
confidence: 99%